Kontribusi Kesejahteraan Guru PAI dalam Kinerja Mengajar pada Masa Pandemi Covid-19 Di SMP Al-Mahrusiyah Ngampel Kota Kediri - Thahiriyah, Fithriyah; Rahman, Marita Lailia (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2022)
In early 2020 the world was shocked by the spread of the coronavirus disease 2019 (COVID-19) which infects several countries around the world including; Indonesia. UNESCO also said that nearly 1,6 billion students and more than 63 million teachers worldwide have experienced school closures due to the COVID-19 pandemic. However, in reality online learning is not easy, because many are faced with various problems, such as the limitations of the internet network and the limitations of regulations in Islamic boarding schools that are not allowed to bring Smartphones. Based on this background, the researchers asked the following research questions: (1)Dimensions of the welfare of PAI teachers from the perspective of psychology in teaching performance at SMP Al-Mahrusiyah Ngampel, Kediri (2)Factors that affect the welfare of PAI teachers in teaching performance at SMP Al-Mahrusiyah Ngampel City of Kediri (3)The contribution of the welfare of PAI teachers in teaching performance at SMP Al-Mahrusiyah Ngampel City of Kediri. This research was conducted using qualitative research methods, this type of research will be able to cature various qualitative information that is more detailed and in depth. The qualitative research method that is in accordance with this research is the phenomenological approach.